2013
DOI: 10.1080/00918369.2013.774874
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Campus Climate by Sexual Minorities

Abstract: Previous research has indicated that students who identify as lesbian, gay, bisexual, or transgender (LGBT) often have negative experiences on university campuses due to their sexual orientation or gender identity. Direct and indirect experiences contribute to an overall perception of the campus climate. This study used an online survey to assess students' perceptions of campus climate, their experiences confronting bias, support of family members and friends, and whether they had considered leaving campus. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 13 publications
(18 reference statements)
5
88
1
4
Order By: Relevance
“…This is in contrast to the existing literature on campus climate for sexual minorities (Rankin et al, 2010;Tetreault et al, 2013). The reasons students felt included are discussed below.…”
Section: Social Exclusion With Family Social Exclusion With Family Econtrasting
confidence: 49%
See 2 more Smart Citations
“…This is in contrast to the existing literature on campus climate for sexual minorities (Rankin et al, 2010;Tetreault et al, 2013). The reasons students felt included are discussed below.…”
Section: Social Exclusion With Family Social Exclusion With Family Econtrasting
confidence: 49%
“…Despite the fact that the student affairs professional purpose is to educate the whole student, sexual minorities still remain virtually invisible (Rankin et. al 2010;Tetreault, Fette, & Meidlinger, 2013).…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous publication (Auerbach et al, ), these students reported high rates of mental disorders compared with other college students, which is unsurprising given that prior to arriving on college campus, many are subject to family rejection, bullying, and social isolation (Dean et al, ; Heatherington & Lavner, ). Further, once on college campus, these students are frequently marginalized and harassed (Rankin, ; Tetreault, Fette, Meidlinger, & Hope, ). Despite the greater incidence of mental disorders and comorbidity, transgender and sexual minority students are often less likely to utilize counseling services (e.g., Beemyn, Curtis, Davis, & Tubbs, ).…”
Section: Discussionmentioning
confidence: 99%
“…Stroup, Glass, and Cohn (2014), for example, conducted a qualitative study of 56 LGBTQ students attending rural colleges in the United States and found that more than half of the participants reported having experienced an act of discrimination because of their LGBTQ identity. However, tapping into LGBTQ students’ strengths and activating protective factors, such as positive support networks and an affirming campus environment, can positively affect LGBTQ students’ psychological well‐being during these critical years, as well as their academic and social success (Rankin et al, 2010; Tetreault, Fette, Meidlinger, & Hope, 2013).…”
mentioning
confidence: 99%